Empirical assessment of the environmental Kuznets curve hypothesis in Indonesia, Malaysia, the Philippines, and Thailand using the ARDL and FMOLS techniques - Takashi, Fukuda (Energy Economics Letters, 2023)
The purpose of the present paper is to empirically investigate whether the environmental Kuznets curve (EKC) hypothesis is validated for Indonesia, Malaysia, the Philippines, and Thailand over the period of 1971-2014. The estimation techniques employed are the autoregressive distributed lag (ARDL) and the fully modified ordinary least square (FMOLS), and we conduct the Granger causality tests to draw interpretation. We take CO2 emissions as the dependent variable, and those endogenous variables of economic growth, the square of economic growth, energy consumption, trade openness, and foreign direct investment (FDI), together with the structural break dummy (for the ARDL estimation only). The EKC hypothesis is statistically confirmed for Thailand by both the ARDL and FMOLS estimations, but it is not so for Indonesia, Malaysia, the Philippines. One policy implication is that, regardless of whether the EKC hypothesis is confirmed or not, the four ASEAN countries are required to ensure the compatibility between economic growth and environmental improvement by persistently proposing and implementing effective policies to fight against environmental degradation. Another implication is that, policymakers should consider how to convert their countries from pollution heaven countries to environmentally-friendly ones, correctly evaluating the impact of globalization on economic growth and environmental degradation.